Development of a Technology for Treating Wastewater Contaminated with Nitric Acid. (2nd July 2013) - Hidalgo, Liz Mabel Ríos; Peralta-Suárez, Luis M.; Busto Yera, Yailen
Abstract : The production process of nitroaromatic hazardous compounds, with the generation of acidic wastewater, represents a significant danger for the health and safety of the workers and the environment. The present study is focused on the development of an efficient installation to treat acidic wastewater resulting from the synthesis process of nitroaromatic compound, considering workers safety and environmental criteria. In this research, a detailed study of the different alternatives that can be used for effective and safe treatment of acidic wastewater was performed. The analysis of several technological schemes for the acidic wastewaters neutralization and the selection of the most feasible alternative from a technical-economic point of view were carried out. The simulation and mathematical modeling developed in this research represent a significant advance in the knowledge of this process for working in a much more secure form. The technological scheme of the process was defined, and the design of the main and auxiliary equipment as well as the piping system was carried out using different computational programs. Finally, this paper proposes a technological design for the treatment of acidic wastewater generated by the production process of nitroaromatic compound, which represents the basic criteria for the further design, construction, and equipment installation of the plant.